FORMULATING BUSINESS STRATEGY: A CASE OF TUTORING AGENCY IN INDONESIA - Zulkifli, Zulkifli; Wandebori, Harimukti (Universitas Brawijaya, Indonesia, 2018)
PT. XYZ Indonesia is a holding company with a collection of thebusiness unit that has a primary focus on education. One of their business units is XYZthat is an education consultant or tutoring agency. The main problem faced by XYZ is their target revenue in 2017 has not been reached or only 70% realization of total target revenue. In this research, use strategic management process to formulate appropriate strategies for XYZin order to achieve their target. Primary and secondary data collection techniques consisting of aquestionnaire, interview, research internet, document review, and company report. This research results in 9 strategies to increase their sales and market shares including corporate, business, and functional level strategy. The implementation plan of the new proposed strategies implemented by its priority to solve the issues. Suggestion for subsequent research was to add other tools in the environmental scanning and strategy formulation phase to deepen the analysis result. Also can use another performance management framework to evaluate the strategies.